Purificación y amplificación de ADN genómico en escamas de la serpiente Bothrops atrox “jergón” (Ofidia: Viperidae) - Rojas y Cols., Rommel (2019)
Molecular research demand the creation of new protocols and permit the obtain a high quality DNA in the most quantity of species and know the genetic diversity, for that objective of the present research was obtained the purification and amplification of scales DNA in the snake Bothrops atrox. the scales were recollected in the field using the visual encounter survey [5] The For the purification of the DNA was modification the protocol [4], the DNA purity was verifiable for the electrophoretic method and it quality and concentration for spectrophotometry, the amplification was carried for Polymerase chain reaction-PCR using random primers. The results show the successful DNA purification, showing an acceptable quality ratio (2) and concentration (585.85 µg/mL), at the same time was made the amplification of DNA for PCR. We conclude indicating the useful of this technique for the purification of high quality DNA from snake´s scales for molecular and genetic research.